2018
DOI: 10.1037/xhp0000466
|View full text |Cite
|
Sign up to set email alerts
|

Integration of serial sensory information in haptic perception of softness.

Abstract: Redundant estimates of an environmental property derived simultaneously from different senses or cues are typically integrated according to the maximum likelihood estimation model (MLE): Sensory estimates are weighted according to their reliabilities, maximizing the percept's reliability. Mechanisms underlying the integration of sequentially derived estimates from one sense are less clear. Here we investigate the integration of serially sampled redundant information in softness perception. We developed a metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 73 publications
9
39
0
Order By: Relevance
“…Specifically, the Serial Weighted Average Model scored slightly higher than the other two average models. This result is consistent with the results found in the work of Metzger et al [11]. They found that the nervous system attributes decreasing weights to the different stiffness levels based on their serial placement in the probing sequence, with the highest weight given to the stiffness level experienced first and the lowest to the last.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Specifically, the Serial Weighted Average Model scored slightly higher than the other two average models. This result is consistent with the results found in the work of Metzger et al [11]. They found that the nervous system attributes decreasing weights to the different stiffness levels based on their serial placement in the probing sequence, with the highest weight given to the stiffness level experienced first and the lowest to the last.…”
Section: Discussionsupporting
confidence: 92%
“…Serially Weighted Averagebased on [11], in trials in which the comparison force field preceded the standard, unequal weights were attributed to the different stiffness levels, with the highest weight given to the first stiffness level and the lowest to the last stiffness level. On the other hand, if the standard was presented first, all eight stiffness levels were given equal weighting.…”
Section: Models For Serial Stiffness Levels Integrationmentioning
confidence: 99%
See 2 more Smart Citations
“…This is qualitatively in line with the threshold predictions but was not quantitatively analyzed and thus is not conclusive. Importantly, results from Metzger, Lezkan, and Drewing (2017) are at odds with the prediction of equal weights in the integration of sequential haptic information. The authors investigated softness discrimination, where people typically indent a soft stimulus repeatedly, and determined the weights of indentation-specific softness estimates for the first and the second stimulus in a trial.…”
mentioning
confidence: 98%